The Effects of Tootling via ClassDojo on Student Behavior in Elementary Classrooms. Issue 1 (1st March 2019) - Dillon, Melissa B. McHugh; Radley, Keith C.; Tingstrom, Daniel H.; Dart, Evan H.; Barry, Christopher T.
Abstract: The current study was designed to evaluate the effects of a tootling intervention, in which students report on peers' appropriate behavior, modified to incorporate ClassDojo technology, on class-wide disruptive behavior and academically engaged behavior. An A-B-A-B withdrawal design was used to evaluate the effects of the intervention in 3 fifth-grade classrooms. Student-produced tootles were recorded using the ClassDojo website and displayed to students via projector. Reinforcement for tootling was provided through an interdependent group contingency based on the number of tootles produced. Results indicated substantial and meaningful decreases in class-wide disruptive behaviors and increases in academically engaged behaviors during intervention phases compared to baseline and withdrawal phases across all three classrooms. Limitations, implications for practice, and directions for future research are discussed.